IMPLEMENTATION OF FAMILY FUNCTIONS IN SINGLE FATHERS IN KAMPAR, RIAU PROVINCE - Anna Zahirah; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to show how single fathers are carrying out family functions from five existing family functions. This research was conducted in Kota Baru Village, Tapung Hilir District, Kampar Regency in Riau Province with a focus on the implementation of family functions in a single area. In this study, the method used is qualitative descriptive, where data is collected through documentation and in-depth interviews. From the results of the research conducted, it was found that in the implementation of family functions, they (single fathers) can carry out these functions even though they are not optimal due to various obstacles they face. The obstacles they experience are obstacles in managing working time with time taking care of the household, multitasking obstacles where single fathers are somewhat minimal related to these skills, obstacles in skills in taking care of children, especially related to the needs of girls. From the results of this study, It can be concluded that in the implementation of family functions carried out by single fathers in Kota Baru Village, especially by five (5) subjects/informants with five (5) family functions, they are all carried out or carried out by each of them in a different way even though it is not optimal due to various existing obstacles. Except for the economic function which is one of the decisive aspects in carrying out other functions, although they carry it out, the way they carry it out depends on their economic conditions.